Variations among 5 European countries for curative treatment of resectable oesophageal and gastric cancer: A survey from the EURECCA Upper GI Group (EUropean REgistration of Cancer CAre). Issue 1 (January 2016) - Messager, M.; de Steur, W.O.; van Sandick, J.W.; Reynolds, J.; Pera, M.; Mariette, C.; Hardwick, R.H.; Bastiaannet, E.; Boelens, P.G.; van deVelde, C.J.H.; Allum, W.H.; ,
Abstract: Introduction: EURECCA (EUropean REgistration of Cancer CAre) is a network aiming to improve cancer care by auditing outcome. EURECCA initiated an international survey to share and compare patient outcome for oesophagogastric cancer. The present study assessed how a uniform dataset could be introduced for oesophagogastric cancer in Europe. Methods: Participating countries presented data using common data items describing patients', disease, strategies, and outcome characteristics. Patients treated with curative surgery for squamous cell carcinoma (SCC) or adenocarcinoma (ACA) were included. Results: United Kingdom, the Netherlands, France, Spain and Ireland participated. There were differences in data source ranging from national registries to large collaborative groups. 4668 oesophagogastric cancer cases over a 12 months period were included. The predominant histological type was ACA. Disease stage tended to be earlier in France and Ireland. In oesophageal and junctional cancers neoadjuvant chemoradiotherapy was preferred in the Netherlands and Ireland contrasting with chemotherapy in the UK and France. All countries used perioperative chemotherapy in gastric cancer but 1/3 of patients received this treatment. The mean R0 resection rate was 86% for oesophageal and junctional resections and 88% for gastric resections. Postoperative mortality varied from 1% to 7%. Conclusion: This European survey shown that implementing a uniform treatment and outcome data format of oesophagogastric cancer is feasible. It identified differences in disease presentation, treatment approaches and outcome, which need to be investigated, especially by increasing the number of participating countries. Future comparisons will facilitate developments in treatment for the benefit of patient outcomes.